Resisting moral wiggle room: How robust is reciprocity? - Joël van der Weele; Julija Kulisa; Michael Kosfeld; Guido Friebel (Institute for the Study of Labor (IZA), 2010)
Several studies have shown that dictator-game giving declines substantially if the dictator can exploit situational excuses for not being generous. In this experimental study we investigate if this result extends to more natural social interactions involving reciprocal behavior. We provide the second mover in a reciprocal game with an excuse for not reciprocating, an excuse which has previously been shown to strongly reduce giving in dictator games. We do not find that the availability of the excuse has any effect at all on reciprocal behavior, and conclude that reciprocity is a more stable disposition than dictator game generosity.
Keywords: C72; C9; 330; reciprocity; moral wiggle room